Facing Workplace Adversities With Enhanced Level Of Resilience With Mindfulness Practice As Intervention – The Study On Generation Y Employees - Vincent Kim Seng OH; Abdullah Sarwar; LAI Ming Ming; YEAP Peik Foong; Gowrie Vinayan; Niaz PERVEZ (Communications of International Proceedings, 2022)
Purpose: This conceptual paper explores the relationship between psychological well-being and resilience using mindfulness as the mediating variable. This paper shows that with mindfulness intervention, Generation Y employees can enhance their level of resilience to face and overcome challenges in their workplace. Design/methodology/approach: The author reviewed related literature by examining the relationship between psychological well-being and resilience and the positive connection with mindfulness. Research Implication: This paper can guide scholars to initiate empirical studies based on enhancing the level of resilience and examining the influence of mindfulness. Originality/value: This conceptual paper provides theoretical insights into the importance of resilience and shows the connection with mindfulness intervention to enhance the resilience of Generation Y employees in the workplace. This paper will deeply encourage scholars to study mindfulness intervention for enhanced workplace resiliency.
Keywords: Psychological well-being; Mindfulness; Resilience; Workplace; Generation Y